Caracterización térmica y técnica del ladrillo multiperforado a nivel de laboratorio (2020)
The ceramics industry in Norte de Santander is recognized for the quality of the raw material that the products offer. However, the guild has limited itself to the mass production of units to satisfy the construction market, leaving aside research and innovation fields to develop new proposals. The characterization of multiperforated brick MB at laboratory level is a thermal and technical referent of a conventional product and positioned in the construction world. The product was developed on a laboratory scale by extrusion in clay and coffee dust in the CIMAC Ceramic Materials Research Center from the Francisco de Paula Santander University, in order to characterize the MB physical and mechanical properties such as linear contraction, mass losses, determination of efflorescence, resistance to compression, dimensions, water absorption, initial rate of capillarity, porosity and apparent specific weight at the laboratory level. In parallel, it was validated thermally through simulations using the finite element method performed in the ANSYS R16 software to identify the energy behavior by transfer and heat fluxes. This research is the starting point for future projects focused on the design of ceramic products. The results provide technical and thermal data to develop new innovative products that contribute to sustainability